PENDIDIKAN MULTIKULTURAL DAN PENANAMAN NILAI-NILAI MODERASI ISLAM DI KALANGAN AHLUSSUNNAH WA AL JAMA’AH - Ridlwan, Burhanuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article intends to examine multicultural education and the cultivation ofmoderating values among the Ahlus Sunnah wa al Jama'ah. Through literature studies areproduced First, the nature of multicultural education is: An array of beliefs andexplanations to recognize and assess the importance of cultural and ethnic diversity in theform of lifestyles, social experiences, personal identities, and educational opportunities ofindividuals and groups, with the primary goal of change the structure of educationalinstitutions so that students, both students who are members of groups, races, ethnicities,and diverse cultures can have equal opportunities in getting treatment and appreciation.Second, the moderating values of Islam as contained in the Medina charter: The attitudeof an egalitarian society, mutual respect, openness, law enforcement and justice,tolerance, deliberation and dialogue. and mutual understanding as in Q.S. al-Hujurat: 13,inclusive attitude in social interaction as in Q.S. al Mumtahanah: 8-9, open attitude andspaciousness as shown by the Prophet SAW when greeting Najran's Christian messenger.Third: multicultural education and the planting of moderating values of Islam among theahlus sunnah wa al-jama'ah are manifestations in the real form of the principles ofahlussunnah wa al-jama'ah (aswaja) in the form of: Tasawuth, Tawazun, Ta ' adul, andtasamuh.Keywords: Multicultural Education, Moderating Values of Islam, and Ahlussunah Wa al Jama'ah